Effects of the Upward Influence Strategies on the Communication Media Selection - Cho, Namjae; Park, Kiho; Su, Che-Jen (Contemporary Management Research, 2008)
In asymmetric interpersonal relationships between a manager and the employee, the media selection behavior under formal or informal context is likely influenced by the upward influence strategy of an employee. According to increasing the usage of online communication media such as electronic mail, internet bulletin board, and chat software and so forth, the styles of media selection have been also changed. Although many studies related to the usage of offline-oriented communication methodologies in organization, have been performed, there must not be enough studies for media selection behavior in online and offline circumstances. This study investigates the relevance between the upward influence tactics and the media selection behaviors in specific circumstances like benevolence and conflict. The research findings indicate the rational strategy person usually prefers FTF(face-to-face) communication to others under benevolent and informal/formal context. On the other hand, the soft strategy person more often makes choices the documented communication, as one of asynchronous media. But, under the conflict context, there were no difference between groups in media selection behavior. We conclude that the media selection behavior will be affected by the personal upward influence strategy and the interpersonal relationship. This implication can give contribution to the organizations considering how to improve the effectiveness in upward and downward communication. Keywords: Upward Influence Strategy, Media Selection Theory, Formal/Informal Communication, Synchronous/Asynchronous Media